Albino Leaf1 That Encodes the Sole Octotricopeptide Repeat Protein Is Responsible for Chloroplast Development . Issue 2 (22nd April 2016) - Zhang, Zemin; Tan, Jianjie; Shi, Zhenying; Xie, Qingjun; Xing, Yi; Liu, Changhong; Chen, Qiaoling; Zhu, Haitao; Wang, Jiang; Zhang, Jingliu; Zhang, Guiquan
Abstract : An octotricopeptide repeat protein regulates chloroplast development by coordinating the transcription and translation of chloroplast associated genes in rice. Abstract: Chloroplast, the photosynthetic organelle in plants, plays a crucial role in plant development and growth through manipulating the capacity of photosynthesis. However, the regulatory mechanism of chloroplast development still remains elusive. Here, we characterized a mutant with defective chloroplasts in rice ( Oryza sativa ), termed albino leaf1 ( al1 ), which exhibits a distinct albino phenotype in leaves, eventually leading to al1 seedling lethality. Electronic microscopy observation demonstrated that the number of thylakoids was reduced and the structure of thylakoids was disrupted in the al1 mutant during rice development, which eventually led to the breakdown of chloroplast. Molecular cloning revealed that AL1 encodes the sole octotricopeptide repeat protein (RAP) in rice. Genetic complementation of Arabidopsis ( Arabidopsis thaliana ) rap mutants indicated that the AL1 protein is a functional RAP. Further analysis illustrated that three transcript variants were present in the AL1 gene, and the altered splices occurred at the 3′ untranslated region of the AL1 transcript. In addition, our results also indicate that disruption of the AL1 gene results in an altered expression of chloroplast-associated genes. Consistently, proteomic analysis demonstrated that the abundance of photosynthesis-associated proteins is altered significantly, as is that of a group of metabolism-associated proteins. More specifically, we found that the loss of AL1 resulted in altered abundances of ribosomal proteins, suggesting that RAP likely also regulates the homeostasis of ribosomal proteins in rice in addition to the ribosomal RNA. Taken together, we propose that AL1, particularly the AL1a and AL1c isoforms, plays an essential role in chloroplast development in rice.